Aḥmad b. Ḥanbal's Legal Opinions on the Fight against Bābak's Uprising: "I don't know of anyone who is more harmful to Islam than he, the evil wretch" - al-Sarhan, Saud (Journal of Abbasid Studies, 2019)
In this article, Aḥmad b. Ḥanbal's role in the fight against Bābak's uprising and his legal opinions on the legitimacy and rules of this fight are presented. Normally reticent in all matters political, Ibn Ḥanbal took an uncharacteristically strong stance against Bābak, claiming he did not know of anything "more harmful to Islam" than Bābak and Khurramism. Focus in the article is on how Ibn Ḥanbal regarded Babāk's revolt and why he took an active role against it despite what could be called his general attitude of political quietism.